Delineation of flood-prone areas using Digital Elevation Model (DEM) in Kuala Krai, Kelantan. Issue 1 (August 2021) - Anis-Athirah, B N; Mohd-Fariz, A R; Bam, H N R; Majid, S; Muhammad, M; Jemali, N J N
Abstract: Kelantan is one of the states that experience flood events annually including the Kuala Krai district. Flooding has a severe impact on roads, villages, farms, and people's livelihoods. Early detection of flood-prone areas is essential in detecting the specific area. This study aimed to map a flood-prone area based on evaluation of terrain characteristics include elevation, aspect, slope, contour and hill shade of the Kuala Krai area. The raster data of DEM with 50 m resolution and hydrological data were evaluated to create a potential flood map. A flood-prone map is created by overlaying terrain features with flood criteria of a gentle slope with contour < 250 m and degree of slope less than 10, flat surface in aspect and consideration of hill shade factors. The map was also supported by vector data of rivers network that cross the Kuala Krai area. 56% of the Kuala Krai area facing a moderate risk of flood occurrence, while 41 % of the areas are in a dangerous state and are predicted to be at a high risk of flood. This can be concluded that the areas with low elevation, adjacent to rivers, are the places where actions need to be taken by the experts to overcome the disaster in the future.